Intellectual capital and strategic decisions: an integrative approach - Kučinskienė, Marija; Broniukaitis, Romualdas (Information & Media, 2017)
In a dynamic and complex market, tangible assets, which often produce only short-term effects, cease to be the critical source of competitive advantage against competitors. Instead, nowadays more emphasis is placed on intellectual competitiveness, which is achieved by the ability to make strategic decisions on business development that are adequate to the changes in the complex and dynamic external environment. An approach based on knowledge resources forms the theoretical background of this study. Its main assumption is that intangible resources are the strategic asset that plays the central role in creating a long-term competitive advantage for organizations. The article emphasises that although intellectual capital and knowledge management are rather extensively discussed in various contexts, the available theoretical and empirical studies are often fragmented. Current research lacks a scientifically-based, integrative approach, which would reveal broader theoretical assumptions that take into account current developments. The article presents an integrative model, built on conceptual theoretical insights that include three components: strategic decisions, intellectual capital and knowledge management. The model broadens the field of research on intellectual capital not only in the addition of strategic dimension as its essential component that influences creation of added value in organizations, but also in its emphasis on the importance of integrating the strategy of intellectual capital with knowledge management. The model also illustrates the link between the components of intellectual capital and processes of knowledge management in the context of strategic management. An assumption is made that the constructed complex research model will provide new insights for scientific research at the theoretical level, while its practical implementation would assist organizations in their strategic development and help to increase the produced added value.
Keywords: ...